(untitled) (Web of Teachers: Inderscience Research, 2024)
This article considers the issues of improving the educational process for children with special needs within the framework of “Kind Schools”. The effectiveness of person-oriented and game-based educational methods, their impact on the intellectual, psychological and social development of children are studied. In addition, the article analyzes the role of differentiated education, project approaches, the use of technologies and game methods in increasing motivation and interactivity. Methods for adapting the educational process to individual needs and creating an effective learning environment are highlighted through these methods.